Tantangan Radikalisme dan Ekstremisme: Kajian Kritis Terhadap Ekstremisme Perspektif Moderasi Beragama - Maisari, Ayu (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2025)
The phenomena of radicalism and extremism in the name of religion have become serious challenges to social life, education, and religiosity in Indonesia. Narrow, exclusive, and intolerant religious understandings often develop within both formal and informal educational spaces, and are further exacerbated by the influence of digital media. This study aims to critically examine the meaning, characteristics, and causal factors of radicalism and extremism, while offering religious moderation as an alternative approach to address these challenges. Using a qualitative library research method, the data were analyzed descriptively and critically through relevant academic literature. The findings indicate that radicalism and extremism stem from various factors such as socio-political injustice, religious emotions, cultural clashes, anti-Western sentiments, and weak governmental policies. Religious moderation, which emphasizes wasatiyyah (balance), tolerance, and openness, is viewed as a strategic solution for shaping an inclusive and peaceful religious paradigm. Religious education that instills the values of moderation from an early age is crucial to preventing the growth of intolerant ideologies and strengthening the ideological resilience of society in facing the currents of global radicalism.